Breastfeeding: individual choice and collective responsibility - Pérez Castillo, Rosa Goergina (2025)
Introduction: Breastfeeding (BF) can be understood as a social learning process, in which there are various factors that influence the forms, times, periods and perceptions surrounding breastfeeding. This form of feeding is constructed and modified according to the social, economic, political, labor and cultural environment, which has effects on the health of mothers and their children. Proposition: The above, leads to reflect on the fact that BF is a collective responsibility that requires the active participation of all social sectors, with the objective of promoting its benefits on the health of the population. Arguments for discussion: This paper analyzes the importance of its social and cultural dimensions, and how these actually represent the greatest difficulties that women who decide to maintain BF must overcome, it also reflects on intervention programs and how these have focused primarily on women, considering their techniques, knowledge, emotions, in some cases, their support networks, however, little recognition is given to other factors of greater hierarchy that determine the decision around such feeding practice. Conclusions: Breastfeeding is a complex practice influenced by social, economic, political, cultural, and labor determinants. Its understanding and promotion require a comprehensive approach and broad discussion that extends beyond individual advocacy.